2013
DOI: 10.1128/ec.00028-13
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Mitogen-Activated Protein Kinase Phosphatase Implicated in Regulating Transition from Pre-S-Phase Asexual Intraerythrocytic Development of Plasmodium falciparum

Abstract: Intraerythrocytic development of the human malaria parasite Plasmodium falciparum appears as a continuous flow through growth and proliferation. To develop a greater understanding of the critical regulatory events, we utilized piggyBac insertional mutagenesis to randomly disrupt genes. Screening a collection of piggyBac mutants for slow growth, we isolated the attenuated parasite C9, which carried a single insertion disrupting the open reading frame (ORF) of PF3D7_1305500. This gene encodes a protein structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 68 publications
2
17
0
Order By: Relevance
“…To establish whether the heat shock phenotype was directly due to insertion in the PfMKP1 coding sequence, the PB-2 mutant was complemented with an episomal copy of the PfMKP1 gene with its native 5′ UTR and a 3′ three-hemagglutinin tag, followed by an HRP3 3′ UTR. Reverse transcription-PCR previously confirmed that the complemented line reintroduced the expression of PfMKP1 RNA (14), and PfMKP1 protein expression was confirmed in wild-type NF54 and the complemented mutant by Western blotting with a custom monoclonal antibody (anti-PfMKP1), while the PB-2 mutant showed no expression (Fig. 3A).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…To establish whether the heat shock phenotype was directly due to insertion in the PfMKP1 coding sequence, the PB-2 mutant was complemented with an episomal copy of the PfMKP1 gene with its native 5′ UTR and a 3′ three-hemagglutinin tag, followed by an HRP3 3′ UTR. Reverse transcription-PCR previously confirmed that the complemented line reintroduced the expression of PfMKP1 RNA (14), and PfMKP1 protein expression was confirmed in wild-type NF54 and the complemented mutant by Western blotting with a custom monoclonal antibody (anti-PfMKP1), while the PB-2 mutant showed no expression (Fig. 3A).…”
Section: Resultsmentioning
confidence: 68%
“…The complemented piggyBac mutant was made previously (14). The complemented piggyBac mutant was maintained in medium with 2 µg/ml blasticidin D to maintain the episome.…”
Section: Methodsmentioning
confidence: 99%
“…3B). To rule out the possibility of additional, unknown piggyBac insertions in the genome, we aligned one file of the paired reads to the transposon sequence and the pair file to the genome (and vice versa) to see where each transposon-aligning paired read mapped (35). Paired ends were found to align only to the Maf1 locus or to regions of the genome used as regulatory sequences within the transposon itself (such as the calmodulin promoter or the HrpII 3′ untranscribed region [3′UTR]) (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Paired ends were found to align only to the Maf1 locus or to regions of the genome used as regulatory sequences within the transposon itself (such as the calmodulin promoter or the HrpII 3′ untranscribed region [3′UTR]) (Table S1). Additionally, we analyzed the PB-11 genome for single nucleotide polymorphisms (SNPs) and indels within all annotated open reading frames in the genome but found none of significance compared to the parental line or a sister piggyBac insertion mutant sequenced previously (35) (Table S2). The latter results support the notion that any phenotype observed in the PB-11 mutant line is a consequence of the transposon insertion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation